A Theory of Challenge and Threat States in Athletes: A Revised Conceptualization - Meijen, Carla; Turner, Martin; Jones, Marc V.; Sheffield, David; McCarthy, Paul (Frontiers in Psychology, 2020)
The Theory of Challenge and Threat States in Athletes (TCTSA) provides a psychophysiological framework for how athletes anticipate motivated performance situations. The purpose of this review is to discuss how research has addressed the 15 predictions made by the TCTSA, to evaluate the mechanisms underpinning the TCTSA in light of the research that has emerged in the last ten years, and to inform a revised TCTSA (TCTSA-R). There was support for many of the 15 predictions in the TCTSA, with two main areas for reflection identified; to understand the physiology of challenge and to re-evaluate the concept of resource appraisals. This re-evaluation informs the TCTSA-R which elucidates the physiological changes, predispositions, and cognitive appraisals that mark challenge and threat states. First, the relative strength of the sympathetic nervous system response is outlined as a determinant of challenge and threat patterns of reactivity and we suggest that oxytocin and neuropeptide Y are also key indicators of an adaptive approach to motivated performance situations and can facilitate a challenge state. Second, although predispositions were acknowledged within the TCTSA, how these may influence challenge and threat states was not specified. In the TCTSA-R it is proposed that one’s propensity to appraise stressors as a challenge that most strongly dictates acute cognitive appraisals. Third, in the TCTSA-R a more parsimonious integration of Lazarusian ideas of cognitive appraisal and challenge and threat is proposed. Given that an athlete can make both challenge and threat primary appraisals and can have both high or low resources compared to perceived demands, a 2x2 bifurcation theory of challenge and threat is proposed. This reflects polychotomy of four parts; high challenge, low challenge, low threat, and high threat. For example, in low threat, an athlete can evince a threat state but still perform well so long as they perceive high resources. Consequently, we propose suggestions for research concerning measurement tools and a reconsideration of resources to include social support. Finally, applied recommendations are made based on adjusting demands and enhancing resources.